Exploring the drivers of social media marketing in Malaysian islamic banks: An analysis via Smart PLS approach - Mohd Thas Thaker, Hassanudin *; Ahmad, K.; Abdollah, A. M.; Hafezali, I. H.; Mohd Thas Thaker, M. A.; Anwar, A. P. (Emerald, 2020)
Purpose: This paper aims to attempt to investigate and test the factors related to social media advertisement that could forecast the intention to subscribe to Islamic banking products in Malaysia. Design/methodology/approach: The research framework used in this study is guided by the Unified Theory of Acceptance and Use of Technology (UTAUT). The questionnaire method was used to collect data from 360 social media users and partial least square (PLS) analysis was carried out for the model’s validation. Findings: The analytical results showed that perceived relevance, informativeness and perceived expectancy were found to have a statistical relationship with the purchase intention of Islamic banking products via a social media platform. Practical implications: The study offers a practical implication in which the findings prove as helpful means for Islamic financial institutions to discover paramount techniques to retain existing customers and at the same time encourage potential new customers to subscribe to their products. Originality/value: Deficiency of research focusing on social media marketing, especially the incorporation of the UTAUT model was observed in the literature. Thus, this paper offers additional literature on social media marketing and elucidates their role in Islamic banking industry, particularly from the Malaysian context. This research is considered to be among the primary attempts to examine the drivers of social media marketing and customers’ intention to subscribe to Islamic banking products in Malaysia.